2023
DOI: 10.1038/s41598-023-32702-5
|View full text |Cite
|
Sign up to set email alerts
|

Aldose reductase inhibition decelerates optic nerve degeneration by alleviating retinal microglia activation

Abstract: As part of the central nervous system (CNS), retinal ganglion cells (RGCs) and their axons are the only neurons in the retina that transmit visual signals from the eye to the brain via the optic nerve (ON). Unfortunately, they do not regenerate upon injury in mammals. In ON trauma, retinal microglia (RMG) become activated, inducing inflammatory responses and resulting in axon degeneration and RGC loss. Since aldose reductase (AR) is an inflammatory response mediator highly expressed in RMG, we investigated if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 94 publications
0
1
0
Order By: Relevance
“…Additionally, using a natural small molecule to inhibit aldose reductase was found to suppress microglia and macrophage migration and inflammatory cytokine secretion in mouse eyes [106,107]. Studies also showed that aldose reductase inhibition alleviated microglia activation triggered by beta-amyloid [66] and optic nerve injury [108], suggesting that aldose reductase blockade plays a protective role in the CNS and may be a therapeutic avenue for OPG. Table 1 is presented below.…”
Section: Targeting the Microenvironmentmentioning
confidence: 96%
“…Additionally, using a natural small molecule to inhibit aldose reductase was found to suppress microglia and macrophage migration and inflammatory cytokine secretion in mouse eyes [106,107]. Studies also showed that aldose reductase inhibition alleviated microglia activation triggered by beta-amyloid [66] and optic nerve injury [108], suggesting that aldose reductase blockade plays a protective role in the CNS and may be a therapeutic avenue for OPG. Table 1 is presented below.…”
Section: Targeting the Microenvironmentmentioning
confidence: 96%
“…Studies have shown that increased AR activity is localized in, among others, pericytes, retinal endothelial cells, ganglion cells, Müller cells, retinal pigment epithelial cells and neurons. AR hyperactivity is involved in destruction of retinal cells [41]. Furthermore, the aldose reductase gene is characterized with the largest number of polymorphisms associated with DR [42].…”
Section: Disorders Of the Polyol Pathwaymentioning
confidence: 99%
“…Studies have shown that increased AR activity is localized in, among others, pericytes, retinal endothelial cells, ganglion cells, Müller cells, retinal pigment epithelial cells, and neurons. AR hyperactivity is involved in the destruction of retinal cells [ 41 ]. Furthermore, the aldose reductase gene is characterized by the largest number of polymorphisms associated with diabetic retinopathy [ 42 ].…”
Section: Introductionmentioning
confidence: 99%